Surface Tension of Binary Liquid Mixture - Saxena, M.C.; Dubey, Poonam; Tripathi, Ashutosh (Asian Journal of Chemistry, 2010)
Surface tension of binary mixture of n-pentane + n-heptane at 293.15 and 323.15 K has been evaluated from the Brock and Bird relation, Eberhart relation and ideal mixing rule and their results have been made to ascertain their validity and assumption on which their derivation are based. The merits and limitation of these relations have also been accessed. The average percentage deviation in the surface tension of the mixture have been used to evaluate extent and magnitude of interaction with in the component of the binary mixture.